Empirical Models Determinant Employee Commitment and Retention Determinants in Shopping Centers: A Case of Indonesia - Sarwani, Sarwani (International Review of Management and Marketing, 2024)
One of the business strategies to win the competition is to recruit the best employees and retain potential employee’s possessed by the organization to still faithful to the organization. Determinants of employee commitment and retention conclude by transient that organizational communication factors, leadership roles, and employee training aspects are highly considered to resolve employee problems in the organization. In this context, an empirical study in the shopping centers to examine the most significant determinants of commitment factors and their implication on employee retention. This paper takes a quantitative approach, with participants from one shopping center in a big city in Indonesia, with of final sample of 169 usable data observations. Data analysis methods take structural equation modeling with a confirmatory factor analysis approach. The findings confirm that organizational communication and training have relevance to employee commitment and retention determinants. Hence, organizations are required to consider those affecting determinants to retain their commitments. It is believed that it adds literature on retention determinants as well as builds awareness in decision-makers on focus to evaluate various leadership styles in manager owns to reach organization sustainability.